2012
DOI: 10.1293/tox.25.225
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Drug Resistance by Lysophosphatidic Acid Receptor-3 in Mouse Mammary Tumor FM3A Cells

Abstract: Lysophosphatidic acid (LPA) acts as a simple phospholipid that interacts with G protein-coupled transmembrane LPA receptors. Recently, it has been reported that each LPA receptor plays different biological roles in acquisition of the malignant property of tumor cells. In this study, to assess the involvement of LPA receptor-3 (LPA3) in cell survival after treatment with anticancer drugs, we generated Lpar3-expressing FM3A-a3A9 cells from mouse mammary tumor FM3A cells and examined the cell survival rate after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Ovarian cancer cells expressing high levels of LPA 1 are more resistant to cisplatininduced apoptosis than cells with low levels of this receptor [6]. Recently, Fukui and colleagues showed that exogenous expression of LPA 3 in hepatocarcinoma and breast cancer cells favor cell survival under cisplatin and doxorubicine treatments [41]. The authors further showed that resistance to these drugs was associated with the activation of Mdr1a and Mdr1b genes controling the expression of the ABC transporter [41].…”
Section: Role Of Lpa In the Resistance To Anti-cancer Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovarian cancer cells expressing high levels of LPA 1 are more resistant to cisplatininduced apoptosis than cells with low levels of this receptor [6]. Recently, Fukui and colleagues showed that exogenous expression of LPA 3 in hepatocarcinoma and breast cancer cells favor cell survival under cisplatin and doxorubicine treatments [41]. The authors further showed that resistance to these drugs was associated with the activation of Mdr1a and Mdr1b genes controling the expression of the ABC transporter [41].…”
Section: Role Of Lpa In the Resistance To Anti-cancer Therapiesmentioning
confidence: 99%
“…Recently, Fukui and colleagues showed that exogenous expression of LPA 3 in hepatocarcinoma and breast cancer cells favor cell survival under cisplatin and doxorubicine treatments [41]. The authors further showed that resistance to these drugs was associated with the activation of Mdr1a and Mdr1b genes controling the expression of the ABC transporter [41]. Blocking LPA 1 and LPA 3 in vivo using Ki16425 also prevent and delay the resistance of renal carcinoma cells to the tyrosine kinase inhibitor sunitinib [34].…”
Section: Role Of Lpa In the Resistance To Anti-cancer Therapiesmentioning
confidence: 99%
“…To avoid or reverse MDR, it is important to know the effect of drugs or compounds on the MDR. Many studies have reported drugs or new compounds with efficient activity to reverse MDR, but a small number of studies have addressed the effect of drugs that can strengthen drug resistance [29,30]. Data on the enhancement of MDR of drugs and the underlying mechanism are still limited.…”
Section: Discussionmentioning
confidence: 99%